Profesionalitas Guru Pendidikan Agama Islam Dalam Peningkatan Proses Pembelajaran - Susilawati, Endang; Ridwan, Ahmad; Madyan, Madyan (Center for Religious Studies and Social Empowerment Foundation, 2023)
This study aims to examine the professionalism of Islamic education teachers in improving the learning process at Madrasah Ibtidaiyah Kurnia Jambi City. The main problem discussed is why the professionalism of Islamic Religious education teachers in improving the learning process at Madrasah Ibtidaiyah Kurnia Jambi City is not optimal. As a qualitative-descriptive research, data collection was carried out using observation, interviews and documentation techniques. While the determination of research subjects using snowball sampling technique. The results of the study show that regarding their professionalism, teachers lack insight in planning lessons. In addition, the problem of discipline and inadequate teacher work experience also adds to the problem of teacher professionalism. An issue that is no less important is that in an effort to improve the learning process, teachers have not paid attention to learning according to content and process standards. Penelitian ini bertujuan untuk mengkaji profesionalitas guru pendidikan Agama Islam dalam peningkatan proses pembelajaran di Madrasah Ibtidaiyah Kurnia Kota Jambi. Permasalahan utama yang dibahas adalah mengapa profesionalitas guru pendidikan Agama Islam dalam peningkatan proses pembelajaran di Madrasah Ibtidaiyah Kurnia Kota Jambi belum optimal. Sebagai penelitian kualitatif-deskriptif, pengumpulan data dilakukan dengan teknik observasi, wawancara dan dokumentasi. Sedangkan penentuan subjek penelitian menggunakan teknik snowball sampling. Hasil penelitian menunjukkan bahwa terkait profesionalitasnya, guru kurang memiliki wawasan dalam merencanakan pembelajaran. Selain itu, persoalan disiplin dan pengalaman bekerja guru yang belum memadai juga menambah persoalan profesionalitas guru. Persoalan yang tidak kalah pentingnya adalah bahwa dalam upaya peningkatan proses pembelajaran, guru belum memperhatikan pembelajaran sesuai standar isi dan proses.